Regulatory development for gene and cell-therapies in the United States - Iglesias-Lopez, Carolina (Henry Stewart Talks, 2023)
US regulation of cell and gene therapies, Gene therapies, Cell-engineering, Cell therapy, Advanced therapies medicinal products (ATMP), Definition and classification of cell and gene therapies, Drug regulatory affairs, Biological drugs, Drug development, Clinical development, Pre-IND meetings, BLA review, Special Protocol Assessment (SPA), Fast track, breakthrough and RMAT Designation